Erosion-resistant high-entropy mosaic structure high-chromium spinel material and preparation method thereof
By preparing high-entropy inlay structure high-chromium spinel material with corrosion resistance, the problem of corrosion of the inner lining of high-temperature furnace in the vitrification treatment of nuclear waste is solved, and the material's high-temperature resistance, peeling resistance and corrosion resistance are improved.
Patent Information
- Application Number
- CN202411510274.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-25
AI Technical Summary
During the process of vitrification of nuclear waste, the furnace materials used in high-temperature furnaces need to have excellent high temperature resistance, hardness and diverse properties to cope with the corrosion problems of the lining of high-temperature glass furnaces.
The high-entropy inlay structure is used to erosion-resistant high-entropy inlay structure. It is prepared by preparing chromium oxide sand, alumina powder, magnesium oxide powder, zirconium oxide powder, titanium oxide powder and polyethylene glycol in a certain proportion, and through ball milling, drying, firing and other processes to form a high-entropy inlay structure.
This material has excellent high temperature resistance, peeling resistance and corrosion resistance, which can effectively solve the corrosion problem of high-temperature glass furnace lining and improve the performance of the overall furnace body.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the field of refractory materials, and in particular relates to a corrosion-resistant high-entropy mosaic structure high-chromium spinel material and a preparation method thereof. Background Art
[0002] Nuclear energy is a great discovery in human history and one of the most promising energy sources for mankind. However, in nuclear industrial production and scientific research, some solid, liquid and gaseous wastes with varying degrees of radioactivity are produced. Although the content of radioactive substances in these wastes is very low, the harm is very great. Ordinary external conditions have no effect on radioactive substances at all. At present, a more energy-saving and environmentally friendly treatment method is the vitrification of nuclear waste; by adding glass melting raw materials to form a glass body, the inclusiveness of glass is used to treat nuclear waste.
[0003] During the vitrification process, a high-temperature furnace is required for vitrification, which puts forward new requirements for the performance and structure of the furnace materials used in the combustion furnace, requiring not only excellent high-temperature resistance, but also hardness and multi-performance. Using the corrosion-resistant high-entropy mosaic structure high-chromium spinel of the present invention as the furnace substrate can improve the performance of the original spinel, thereby improving the efficiency of the overall furnace body. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a corrosion-resistant high-entropy mosaic structure high-chromium spinel material and a preparation method thereof. The corrosion-resistant high-entropy mosaic structure high-chromium spinel is mainly prepared by mixing excellent chromium oxide sand, aluminum oxide powder, magnesium oxide powder, zirconium oxide powder, titanium oxide powder and polyethylene glycol in a certain proportion, and undergoing a process of batching, preheating in an insulation box, high-temperature firing and natural cooling. The corrosion-resistant high-entropy mosaic structure high-chromium spinel has superior performance and good high temperature resistance, anti-flaking and corrosion resistance.
[0005] The present invention prepares the in-situ formed chromium spinel through high entropy treatment, and has the excellent properties of multiple elements, while also increasing the high temperature resistance and corrosion resistance; the preparation process is relatively simple, and the prepared high-entropy mosaic structure high-chromium spinel has excellent performance and can well solve the problem of lining corrosion in high-temperature glass melting furnaces.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is: A corrosion-resistant high-entropy mosaic structure high-chromium spinel material. The raw materials are calculated by weight: 80-90 parts of chromium oxide sand, 5-15 parts of aluminum oxide powder, 5-10 parts of magnesium oxide powder, 1-2 parts of zirconium oxide powder, and 1-2 parts of titanium oxide powder.
[0007] The amount of polyethylene glycol added is 1-3% of the total weight of the original material.
[0008] The amount of binder added is 3-10% of the total weight of the original material.
[0009] The binder is aluminum dihydrogen phosphate and clay; the amount of aluminum dihydrogen phosphate added is 30-50% of the total weight of the binder; the amount of clay added is 50-70% of the total weight of the binder.
[0010] The purity of chromium oxide sand is greater than 95%, the purity of zirconium oxide powder with a particle size of 200 mesh is greater than 99%, the purity of aluminum oxide powder with a particle size of 200 mesh is greater than 99%, and the particle size is ≤5μm.
[0011] The purity of magnesium oxide powder is greater than 98%, and the particle size is ≤3μm.
[0012] The purity of titanium oxide powder is greater than 95%, and the particle size is ≤3μm.
[0013] The purity of polyethylene glycol is >98% and the particle size is ≤120μm.
[0014] A method for preparing a corrosion-resistant high-entropy mosaic structure high-chromium spinel material: Step 1: Mix and dry the raw materials Chromium oxide sand, metal aluminum powder, magnesium oxide powder, zirconium oxide powder and titanium oxide powder are added to a vibration mill in the above weight proportions and ground for 1 to 5 minutes. The mixed ingredients are added with a binder and polyethylene glycol and put into a ball mill for 5 to 20 hours. After being ground into a sticky solid, the mixture is dried at 200° C. for 2 hours to obtain a premix. Step 2: Place the milled ingredients into a mold, extrude and shape them, and then cure and dry the molded block at 110-130°C for 12-18 hours, sinter the dried test block at 1700-1800°C for 1-3 hours, and keep it warm for 1 hour to obtain a corrosion-resistant high-entropy mosaic structure high-chromium spinel.
[0015] The present invention uses a chromium spinel layer as a matrix, and has multiple layers of high-entropy inorganic non-metallic material layers on the chromium spinel layer. The components of these high-entropy material layers are mainly a mixture of multiple inorganic non-metallic materials that have been treated with high entropy, and they are embedded in each other in a disordered crystal structure.
[0016] In the present invention, under high temperature conditions, the raw materials undergo ion diffusion and recombination; divalent and trivalent metal ions are rearranged in the crystal lattice to form crystals with a spinel structure in situ; during the reaction, atoms obtain sufficient energy so that the ions in the crystal lattice can overcome energy barriers to migrate, and a chromium spinel layer is grown in situ.
[0017] The raw material mixing of the present invention comprises firstly uniformly mixing a plurality of inorganic non-metallic materials according to a certain stoichiometric ratio; and then making different particles fully contact with each other by impacting and grinding the raw materials with ball milling media, thereby reducing the particle size and increasing the reaction activity.
[0018] The high temperature sintering of the present invention is to subject the mixed raw materials to high temperature sintering. Under high temperature environment of about 1000-2000°C, the atoms in the material will obtain sufficient energy and undergo intense thermal motion. Atoms of different elements will diffuse and dissolve with each other to form a complex solid solution structure. This process is similar to the mixing of atoms in alloys, which increases the entropy value of the system, thereby achieving high entropy.
[0019] The rapid cooling of the present invention, after sintering, uses a rapid cooling method to fix the high entropy structure. Rapid cooling can inhibit the re-diffusion and ordering process of atoms, so that the high entropy state can be retained.
[0020] The entropy mosaic structure of the present invention is a chromium spinel layer as the bottom layer as the matrix, which plays a role of supporting and combining with the matrix. On the chromium spinel layer, there are multiple layers of high entropy inorganic non-metallic material layers. The components of these high entropy material layers are mainly a mixture of multiple inorganic non-metallic materials that have been treated with high entropy, and they are inlaid with each other in a disordered crystal structure.
[0021] The disordered crystal structure obtained by the present invention means that the arrangement of atoms or ions in the crystal lattice does not have long-range order. In this high-entropy material, atoms of multiple elements are mixed with each other and are not arranged regularly like traditional crystals.
[0022] This disordered crystal structure can bring many advantages. The first is to improve the corrosion resistance of the material. Due to the lack of obvious crystal interfaces and orderly atomic arrangement, it is difficult for corrosive media (such as acids, alkalis, high-temperature molten salts, etc.) to diffuse and erode along specific grain boundaries or atomic layers. Secondly, the disordered structure can increase the hardness and toughness of the material. The random distribution of different elements can hinder the movement of dislocations, thereby increasing the strength of the material. In addition, the high-entropy disordered structure can also make the material have better thermal stability. In a high-temperature environment, the disordered arrangement of atoms can reduce structural damage caused by factors such as thermal expansion.
[0023] In step 1, the mass ratio of material to ball during wet ball milling is 1-5:5-9.
[0024] The chromium oxide sand has high melting point, high chemical stability, high hardness, corrosion resistance, acid and alkali resistance and high temperature stability. The metal aluminum powder has anti-oxidation properties and good ductility, and can act to connect particles to form a stable mosaic structure. The magnesium oxide powder has high fire-resistant insulation performance, good thermal expansion coefficient, high thermal conductivity, and can make the material shape difficult to change at high temperature. The zirconium oxide powder has high thermal stability, wear resistance, corrosion resistance, high hardness, high compressive strength and high thermal conductivity. The titanium oxide powder has a high melting point, strong adhesion, is not easy to chemically react, and has stable properties. The present invention is mainly used for ceramic lining coatings for vitrification treatment of nuclear waste. The present invention utilizes the high melting point and high corrosion resistance of chromium element, and performs high entropy treatment with other elements with different properties to form a layered mosaic structure, which further increases the stability of material properties, realizes the improvement of spinel corrosion resistance and high temperature resistance, and has outstanding technical advancement.
[0025] In step 1, the chromium oxide sand, metallic aluminum powder, magnesium oxide powder, zirconium oxide powder and titanium oxide powder are pre-ball-milled, which not only achieves the purpose of uniform mixing, but also further reduces the particle size of the powder during the grinding process, increases the specific surface area of the powder to a certain extent, reduces the surface activation energy of the particles, and improves the uniformity of the coating.
[0026] The beneficial effects of the present invention are as follows: the present invention wet-ball-mills chromium oxide sand, metal aluminum powder, magnesium oxide powder, zirconium oxide powder, and titanium oxide powder to obtain a premix, and then stirs the premix with a polyethylene glycol solution to obtain a high-chromium spinel. The magnesium-aluminum chromium oxide sand, metal aluminum powder, magnesium oxide powder, zirconium oxide powder, and titanium oxide powder are pre-ball-milled to increase the specific surface area of the powder and reduce the particle surface activation energy; the preparation process of the present invention is relatively simple, and the prepared high-entropy high-chromium spinel has excellent high temperature resistance and corrosion resistance, and good comprehensive performance.
[0027] The high-entropy mosaic structure high-chromium spinel of the present invention is prepared by mixing chromium oxide sand, metal aluminum powder, magnesium oxide powder, zirconium oxide powder and titanium oxide powder in a certain proportion, through batching, preheating in an insulation box, high-temperature firing and natural cooling, and the preparation process is simple.
[0028] The corrosion-resistant high-entropy mosaic structure high-chromium spinel of the present invention has excellent performance, and has a series of advantages such as compact structure, multi-element mosaic, strong corrosion resistance, stable performance, etc. These properties make it occupy an important position in the field of ceramics and refractory materials, and is widely used in material preparation. The chromium element can well enhance the toughness and strength of the material, making it corrosion-resistant, and the high-entropy treatment can well combine the stable mosaics of different elements together, so that it has a combination of multiple properties, thereby solving the problem of insufficient single material properties, and then solving the problem of high requirements for furnace materials in nuclear waste treatment. DETAILED DESCRIPTION
[0029] The present invention is further described in detail below in conjunction with specific embodiments. An embodiment of the present invention provides a corrosion-resistant high-entropy mosaic structure high-chromium spinel material and a preparation method thereof, wherein the purity of chromium oxide sand is greater than 95%, and the particle size is 200 mesh, the purity of zirconium oxide powder is greater than 99%, and the particle size is 200 mesh, the purity of aluminum oxide powder is greater than 99%, and the particle size is ≤5μm, the purity of magnesium oxide powder is greater than 98%, and the particle size is ≤3μm, the purity of titanium oxide powder is greater than 95%, and the particle size is ≤3μm, and the purity of polyethylene glycol is greater than 98%, and the particle size is ≤120μm.
[0030] Example
[0031] Step 1: Mix and dry the raw materials Add 80 parts of chromium oxide sand, 5 parts of metal aluminum powder, 5 parts of magnesium oxide powder, 2 parts of zirconium oxide powder and 1 part of titanium oxide powder in the above weight proportions into a vibration mill and grind for 3 minutes. Add the mixed ingredients to a binder and polyethylene glycol and put them into a ball mill for 5 hours. After grinding into a viscous solid, dry it at 200°C for 2 hours to obtain a premix.
[0032] Among them, the amount of adhesive added is 3% of the total weight of the original material. The adhesives are aluminum dihydrogen phosphate and clay. The amount of aluminum dihydrogen phosphate added is 30% of the total weight of the adhesive; the amount of clay added is 70% of the total weight of the adhesive; and the amount of polyethylene glycol added is 1% of the total weight of the original material.
[0033] Step 2: Preparation of corrosion-resistant high-entropy mosaic structure high-chromium spinel The ball-milled ingredients were placed in a mold and extruded into shape. The formed test block was then cured and dried at 110°C for 12 hours. The dried test block was fired at 1750°C for 1 hour and kept warm for 1 hour to obtain the corrosion-resistant high-entropy mosaic structure high-chromium spinel.
[0034] Example
[0035] Step 1: Mix and dry the raw materials Add 82 parts of chromium oxide sand, 2 parts of metallic aluminum powder, 8 parts of magnesium oxide powder, 5 parts of zirconium oxide powder and 1 part of titanium oxide powder in the above weight proportions into a vibration mill and grind for 3 minutes. Add the mixed ingredients into a binder and polyethylene glycol and put them into a ball mill for 5 hours. After grinding into a viscous solid, dry it at 200°C for 2 hours to obtain a premix.
[0036] Among them, the amount of adhesive added is 5% of the total weight of the original material. The adhesives are aluminum dihydrogen phosphate and clay. The amount of aluminum dihydrogen phosphate added is 40% of the total weight of the adhesive; the amount of clay added is 60% of the total weight of the adhesive; and the amount of polyethylene glycol added is 2% of the total weight of the original material.
[0037] Step 2: Preparation of corrosion-resistant high-entropy mosaic structure high-chromium spinel The ball-milled ingredients were placed in a mold and extruded into shape. The formed test block was then cured and dried at 110°C for 12 hours. The dried test block was fired at 1750°C for 2 hours and kept warm for 1 hour to obtain the corrosion-resistant high-entropy mosaic structure high-chromium spinel.
[0038] Example
[0039] Step 1: Mix and dry the raw materials 90 parts of chromium oxide sand, 2 parts of metal aluminum powder, 2 parts of magnesium oxide powder, 2 parts of zirconium oxide powder and 1 part of titanium oxide powder in the above weight proportions are added into a vibration mill and ground for 5 minutes. The mixed ingredients are added with a binder and polyethylene glycol and put into a ball mill for 10 hours. After grinding into a viscous solid, it is dried at 200°C for 2 hours to obtain a premix.
[0040] Among them, the amount of adhesive added is 7% of the total weight of the original material. The adhesives are aluminum dihydrogen phosphate and clay. The amount of aluminum dihydrogen phosphate added is 50% of the total weight of the adhesive; the amount of clay added is 50% of the total weight of the adhesive; and the amount of polyethylene glycol added is 3% of the total weight of the original material.
[0041] Step 2: Preparation of corrosion-resistant high-entropy mosaic structure high-chromium spinel The ball-milled ingredients were placed in a mold and extruded into shape. The formed test block was then cured and dried at 130°C for 18 hours. The dried test block was fired at 1800°C for 3 hours and kept warm for 1 hour to obtain the corrosion-resistant high-entropy mosaic structure high-chromium spinel.
[0042] Example
[0043] Step 1: Mix and dry the raw materials 90 parts of chromium oxide sand, 1 part of metallic aluminum powder, 5 parts of magnesium oxide powder, 1 part of zirconium oxide powder and 1 part of titanium oxide powder in the above weight proportions are added into a vibration mill and ground for 5 minutes. The mixed ingredients are added with a binder and polyethylene glycol and put into a ball mill for 20 hours. After grinding into a sticky solid, it is dried at 200°C for 2 hours to obtain a premix.
[0044] Among them, the amount of adhesive added is 10% of the total weight of the original material. The adhesives are aluminum dihydrogen phosphate and clay. The amount of aluminum dihydrogen phosphate added is 50% of the total weight of the adhesive; the amount of clay added is 50% of the total weight of the adhesive; and the amount of polyethylene glycol added is 3% of the total weight of the original material.
[0045] Step 2: Preparation of corrosion-resistant high-entropy mosaic structure high-chromium spinel The ball-milled ingredients were placed in a mold and extruded into shape. The formed test block was then cured and dried at 130°C for 18 hours. The dried test block was fired at 1800°C for 3 hours and kept warm for 1 hour to obtain the corrosion-resistant high-entropy mosaic structure high-chromium spinel.
[0046] The corrosion-resistant high-entropy mosaic structure high-chromium spinel prepared in Examples 1-4 was sampled and tested, and the test results of its main chemical composition and physical properties are as follows: Table 1 Physical and chemical properties of corrosion-resistant high-entropy mosaic structure high-chromium spinel
[0047] The physical and chemical properties of the corrosion-resistant high-entropy mosaic structure high-chromium spinel prepared in the above Examples 1-4 are shown in Table 1. From Table 1, it can be seen that the high-entropy mosaic structure high-chromium spinel of the present invention has excellent properties, high temperature resistance, and excellent corrosion resistance, and can effectively improve the performance of the combustion furnace.
[0048] The corrosion-resistant high-entropy mosaic structure high-chromium spinel prepared by the present invention has excellent corrosion resistance. Compared with other preparation methods, this preparation method has the following advantages: the preparation process only requires ball milling, drying, stirring, curing and sintering processes, and the process is simple.
[0049] The above embodiments will help relevant persons in the art to further understand the invention, but they do not limit the invention in any form. Without departing from the scope of the invention defined by the attached claims, various changes in form, details or equivalents made by using the present invention are all within the protection scope of the present invention.
Claims
1. A corrosion-resistant high-entropy mosaic structure high-chromium spinel material, characterized by: The raw materials are calculated by weight as follows: 80-90 parts of chromium oxide sand, 5-15 parts of aluminum oxide powder, 5-10 parts of magnesium oxide powder, 1-2 parts of zirconium oxide powder, and 1-2 parts of titanium oxide powder; the amount of polyethylene glycol added is 1-3% of the total weight of the raw materials; and the amount of adhesive added is 3-10% of the total weight of the raw materials.
2. The corrosion-resistant high-entropy mosaic structure high-chromium spinel material according to claim 1, characterized in that: The binders are aluminum dihydrogen phosphate and clay.
3. The corrosion-resistant high-entropy mosaic structure high-chromium spinel material according to claim 2, characterized in that: The amount of aluminum dihydrogen phosphate added is 30-50% of the total weight of the adhesive; the amount of clay added is 50-70% of the total weight of the adhesive.
4. The corrosion-resistant high-entropy mosaic structure high-chromium spinel material according to claim 1, characterized in that: The purity of chromium oxide sand is >95% and the particle size is 200 mesh.
5. The corrosion-resistant high-entropy mosaic structure high-chromium spinel material according to claim 1, characterized in that: The purity of zirconium oxide powder is >99% and the particle size is 200 mesh.
6. The corrosion-resistant high-entropy mosaic structure high-chromium spinel material according to claim 1, characterized in that: The purity of alumina powder is >99% and the particle size is ≤5μm.
7. The corrosion-resistant high-entropy mosaic structure high-chromium spinel material according to claim 1, characterized in that: The purity of magnesium oxide powder is greater than 98%, and the particle size is ≤3μm.
8. The corrosion-resistant high-entropy mosaic structure high-chromium spinel material according to claim 1, characterized in that: The purity of titanium oxide powder is greater than 95%, and the particle size is ≤3μm.
9. The corrosion-resistant high-entropy mosaic structure high-chromium spinel material according to claim 1, characterized in that: The purity of polyethylene glycol is >98% and the particle size is ≤120μm.
10. The method for preparing a corrosion-resistant high-entropy mosaic structure high-chromium spinel material according to claim 1, characterized in that: Step 1: Mix and dry the raw materials. Add chromium oxide sand, metal aluminum powder, magnesium oxide powder, zirconium oxide powder and titanium oxide powder in the above weight proportions into a vibration mill and grind for 1-5 minutes. Add the mixed ingredients to a binder and polyethylene glycol and put them into a ball mill for 5-20 hours; after grinding into a sticky solid, dry at 200°C for 2 hours to obtain a premix; Step 2: Put the ball-milled ingredients into a mold, extrude them into shape, and then cure and dry the molded blocks at 110-130°C for 12-18 hours. Sinter the dried experimental blocks at 1700-1800°C for 1-3 hours, and keep them warm for 1 hour to obtain a corrosion-resistant high-entropy mosaic structure high-chromium spinel.
Citation Information
Patent Citations
Method for preparing refractory material for hazardous waste incineration rotary kiln with chromium residues / high chromium rejected bricks
CN108046813A
Aluminum and chromium refractory mortar and production method thereof
CN108752026A
Anti-scouring alumina-magnesia spinel brick and preparation method thereof
CN110386808A
Electric smelting zirconium-magnesium-chromium spinel raw material and preparation method thereof
CN116332635A
Chromium-zirconium refractory material, preparation method thereof and chromium-zirconium electrode brick
CN116621578A